Kompetensi Dosen dan Prestasi Belajar Mahasiswa Program Studi D3 Kebidanan Stikes Kuningan - Ai Nurasiah (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Intoduction : Faculty Competence is a set of intelligent action full responsibility should have someone as qualified to be able to carry out the tasks in the a certain field of work. Lecturers competence question is competence lecturer on subjects of Midwifery Care I (ANC) College of Health Sciences Kuningan. Competency lecturer studied include pedagogical, professional competence, personal competence and social competence. Learning achievement is the result of learning is expressed in the form, numbers, letters reflect the results that have been achieved by students in exams Midwifery Care I (ANC). Methods: This research is analytical correlational design. This study population is students of Diploma Studies Midwifery Year of 2008/2009. The sample used is total sampling techniques as many as 81 people. Technique data collecting primary data using questionnaires and secondary data from the competency test values Midwifery Care I (ANC). Result: The results were analyzed using Pearson Product Moment formula and use a formula to determine the contribution coefficient of determination of the variable X to variable Y.Results Person Product Moment Correlation test showed that there is a positive relationship between pedagogical, professional competence, personal competence, social competence with academic achievement. Pedagogical contribution to the achievement of students was 23.5%, 26.7% professional competence, personal competence and social competence 18.2% 12.8%. It is therefore a need to increase the competence of lecturers to obtain maximum student achievement.